A Conceptual Study of User Adoption for Military Lifetime Health Record Systems - Hasimi Sallehudin; Ahmad Firdause Md Fadzil; Rogis Baker (JOIV : International Journal on Informatics Visualization, 2019)
The Ministry of Defence in Malaysia has realized a lot of information technology venturing into the world of healthcare for armed forces. From time to time, the majority of these successful healthcare systems are increasingly aware of the extent and success of its operations. Along with IT growth, there is a need for excellent technical capability as well as integrated, centralized, comprehensive and intensive health information systems for armed forces in Malaysia. However, given the success rate in the application of transverse health information system is very high, it is significant to identify the user adoption factor to increase the success rate. Thus, this paper attempt to identify user adoption factors among the medical and clinical personnel’s which Malaysian Armed Forces Hospital and Clinics should keep in mind, to ensure the success of health record systems’ implementation. In this article, we propose our proposition for the clinician and medical personnel’s adoption model to answer our research problem.